ANALISIS PENERAPAN EARMARKING TAX ATAS PAJAK KENDARAAN BERMOTOR DITINJAU DARI ASAS KEMANFAATAN (BENEFIT PRINCIPLE) PADA PEMELIHARAAN JALAN DI PROVINSI BANTEN TAHUN 2015-2017 - Kurnia Larasati; Yopy Ratna Dewanti (POLITEKNIK LP3I JAKARTA, 2020)
Motor Vehicle Tax is one of the taxes included in the Earmarking Tax policy where the amount of allocation is at least 10% of the proceeds of motor vehicle tax receipts and is used for the construction of transportation infrastructure. This provision is explained in Law No. 28 of 2009. In Banten Province this provision is described in Banten Regional Regulation No. 1 of 2011. Even though it has been set at minimum of 10%, but the problem of road damage is still a lot in some places, due to many vehicles on the highway, which can make accidents and congestion. The Problems that occur due to unfavorable road conditions make a public perception of public services provided by the government. The purpose of this study is to analyze the application of Motor Vehicle Tax allocation in its designation for the construction of transportation facilities and infrastructure in Banten Province. The research method used is a qualitative method descriptive approach. The results of this study indicate that the allocation of 10% PKB cannot yet be fully implemented for the construction and maintenance of road infrastructure in Banten Province. Considering, there are several problems related to the implementation of the policy.Keywords: Earmarking Tax Motor Vehicle Tax, Usability Principle